Lived Experience in Lifestyle Modification of Patients with Old Myocardial Infarction at the University Hospital in Bangladesh - Akter, Mst. Monni; Anowar, Md. Nurul; Akter, Jotsna; Khatun, Fahima; Hasan, Md Mahmudul (KHD-Production, 2023)
Realizing the advantages of lifestyle modification after myocardial infarction (MI) requires active lifestyle change. Sometimes patients find it difficult to follow the recommendations for lifestyle changes, which are crucial for all MI patients to implement in order to lower the risk of secondary attack. This study aimed to explore the real-world experiences of post-MI patients who had changed their lifestyles at a university hospital. This qualitative study was conducted among 20 purposively selected post-MI patients. The patients who had confirmed medical diagnosis as old MI, had been admitted to Bangabandhu Sheikh Mujib Medical University Hospital for more than a week, and had been willing to participate in this study were considered as the study subjects. Data was collected through an open ended semi-structured questionnaire by face-to-face interview. Using qualitative content analysis, the interview transcripts were examined at the same time as the data was being gathered. Out of 20 study subjects, 55% were male and 60% were Muslim. Participants age was ranging from 36-70 years. Two themes, namely adjustment with modified life and maladjustment with normal life emerged as the lived experiences of lifestyle modification of patients with old Myocardial Infarction. It is concluded that patients with post-MI can have both good and bad experiences during the period of lifestyle modification.